2015
DOI: 10.1109/jphotov.2015.2430013
|View full text |Cite
|
Sign up to set email alerts
|

Compact Light-Emitting Diode-Based AAA Class Solar Simulator: Design and Application Peculiarities

Abstract: In this paper, we report on the efficient design of a light-emitting diode (LED)-based AAA class solar simulator, employing only 19 high-power emitters for a usable illuminated area of at least 5 cm in diameter with at least 1 sun irradiance. Such a low number of emitters was achieved by selectively employing secondary optics for several LED groups and taking advantage of wide emission angle for others. The so-called A class spectrum was also achieved for the larger area of more than 6 cm × 6 cm, covering zone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 19 publications
4
10
0
Order By: Relevance
“…The author used low ripple power supply with the constant current control as the LED driver. This is in accordance with the study results of Bazzi [3] and the design of Novickovas [1] and Stuckelberger [12] whose results showed that the uniformity measurements were also in class A. …”
Section: ) Short-term Instability Testsupporting
confidence: 92%
See 4 more Smart Citations
“…The author used low ripple power supply with the constant current control as the LED driver. This is in accordance with the study results of Bazzi [3] and the design of Novickovas [1] and Stuckelberger [12] whose results showed that the uniformity measurements were also in class A. …”
Section: ) Short-term Instability Testsupporting
confidence: 92%
“…This prototype satisfies the highest classifications (better than AAA from 400 to 750 nm) with an illuminated area of 18 cm × 18 cm with the maximum irradiance of about 2,435 W/m 2 Novickovas. [1] reported on an efficient design of a light-emitting diode (LED)-based AAA class solar simulator, employing only 19 high-power emitters for a usable illuminated area of at least 5 cm in diameter with 1 sun irradiance. The number of LEDs used in this design was very low and was able to include several wavelengths of the LED groups (400-950 n.m.) and taking advantage of wide emission angle for others.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations